2005
DOI: 10.1373/clinchem.2005.052324
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Plasma Tumor Marker Identified with Bead-Based Affinity-Fractionated Proteomic Technology

Abstract: Background: There is no plasma marker for detecting oral cancer, one of the most frequent cancers worldwide. We developed a bead-based affinity-fractionated proteomic method to discover a novel plasma marker for oral cancer. Methods: Affinity purification of heparinized plasma with magnetic beads and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis were used to screen potential oral cancer markers. We compiled MS protein profiles for 57 patients with oral can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 35 publications
(26 reference statements)
1
81
1
Order By: Relevance
“…Recently state-of-the-art proteomics technologies have revealed alterations in protein abundance, posttranslational modification and turnover, and spatial and temporal distribution within tumor specimens. Using proteomics approaches, aberrantly expressed proteins have been identified in body fluids (12)(13)(14), frozen or paraffin-embedded tissues (15)(16)(17)(18), and cultured cell lines (19 -22). The fold changes in protein expression in samples from healthy and cancerous states as well as the roles of each protein in disease progression must be determined to identify potential candidates for biomarkers and therapeutic targets.…”
mentioning
confidence: 99%
“…Recently state-of-the-art proteomics technologies have revealed alterations in protein abundance, posttranslational modification and turnover, and spatial and temporal distribution within tumor specimens. Using proteomics approaches, aberrantly expressed proteins have been identified in body fluids (12)(13)(14), frozen or paraffin-embedded tissues (15)(16)(17)(18), and cultured cell lines (19 -22). The fold changes in protein expression in samples from healthy and cancerous states as well as the roles of each protein in disease progression must be determined to identify potential candidates for biomarkers and therapeutic targets.…”
mentioning
confidence: 99%
“…Cheng et al observed the high specificity and sensitivity of the fibrinogen a-chain fragment in oral cancer plasma, suggesting that it may be a clinically useful tumor marker. 45 In this study, the fibrinogen fragment presented higher sensitivity (100%) and specificity (97%) for cancer than the other markers detected, by MALDI ToF/ToF followed by Mascot identification. Previous studies in animal models have shown that inhibition of fibrinogen strongly diminishes the development of metastatic lung cancer, further demonstrating the important role of fibrinogen in sustaining invasion and survival of tumor cells.…”
Section: Plasma and Serum Biomarker Studiesmentioning
confidence: 52%
“…Chemical chromatographic surfaces selectively purify certain subsets of proteins, allowing unbound impurities to be removed by washing with buffers. Proteins are typically enzymatically digested after elution and before matrix-assisted laser desorption/ ionization (MALDI) time of flight (ToF) MS analysis, among other forms of MS. 45 MALDI-ToF MS sensitively and precisely separates target proteins according to their mass-dependent velocities (m/z). Surface enhanced laser desorption/ionization (SELDI) ToF MS uses chip-based protein sample arrays with different chemical chromatographic surfaces to selectively bind proteins with specific chemical properties, such as hydrophobic, cationic-anionic, or metal-binding molecules, whereas nonspecifically bound proteins or impurities are removed by washing with buffers.…”
Section: Pathogenesismentioning
confidence: 99%
“…Various proteomic approaches have been applied to biomarker discovery using biological fluids. It is being interestingly recognized that low mass weight peptides, such as S100A8 and fibrinogen, play an important role in physiological and pathological process and could be used as relevant biomarker candidates (Cheng et al, 2005;Tolson et al, 2006). Recently mass spectrum that directly detects and differentiates short peptides has offered a promising approach for peptidomic biomarker discovery (Alagaratnam et al, 2008;Chinello et al, 2010;Dai et al, 2010;Du et al, 2010;Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%